COLLABORATIVE LEARNING IN ARABIC LANGUAGE LEARNING IN INDONESIA: A SYSTEMATIC LITERATURE REVIEW - Simon, Anis Shalatin; Mutmainah, Fatimah Azzahra; Sarif, Suharia; Annisa, Isna (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2024)
The Education 5.0 era requires learners to acquire both language and communication skills. In light of the contemporary demands, collaborative learning is highly recognized as a strong methodology to improve both linguistic and social competencies, its practice in Arabic language teaching faces huge obstacles. This study is exploring efficient strategies for collaborative learning with Arabic as a target language and the factors influencing successful applications will be scrutinized. This study applies the Systematic Literature Review (SLR) methodology referring to PRISMA guidelines. The findings of this study have indicated that instructional strategies such as Group Discussion, Think Pair Share, and Project-Based Learning do significantly improve listening, speaking, reading, and, most importantly, writing skills. The effectiveness of these strategies is determined by four main factors: pedagogical (teacher competence and instructional design), social (student interaction and environmental support), group dynamics (heterogeneous composition and structured interaction), and technological (technology availability and integration). The presented research emphasizes the need for improved teacher preparation programs, thoughtful instructional design, and equitable student access to the latest technologies in order for the collaborative learning approach in Arabic language instruction to deliver optimal experiences.